2023
DOI: 10.15252/embj.2022113360
|View full text |Cite
|
Sign up to set email alerts
|

A non‐proteolytic release mechanism for HMCES‐DNA‐protein crosslinks

Abstract: The conserved protein HMCES crosslinks to abasic (AP) sites in ssDNA to prevent strand scission and the formation of toxic dsDNA breaks during replication. Here, we report a non‐proteolytic release mechanism for HMCES‐DNA‐protein crosslinks (DPCs), which is regulated by DNA context. In ssDNA and at ssDNA‐dsDNA junctions, HMCES‐DPCs are stable, which efficiently protects AP sites against spontaneous incisions or cleavage by APE1 endonuclease. In contrast, HMCES‐DPCs are released in dsDNA, allowing APE1 to initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…These proteins rapidly capture AP sites located at single-strand/duplex junctions in DNA via rapid thiazolidine formation. These AP–protein adducts are resistant to strand cleavage reactions that otherwise might induce genomic instability. ,,,, After repair synthesis restores the AP–protein adduct to the context of double-stranded DNA, the protein catalyzes its own dissociation from the DNA, leaving the AP site to be repaired via the base excision repair pathway. ,, The slow strand cleavage reactions that we observe for the thiazolidine adducts, with half-lives in the range of 12–60 h, are unlikely to be relevant to the properties of the SRAP proteins because these DNA–protein adducts are relatively short-lived, , and the microenvironment surrounding the thiazolidine residue in the active site of these proteins disfavors strand cleavage …”
Section: Discussionmentioning
confidence: 90%
“…These proteins rapidly capture AP sites located at single-strand/duplex junctions in DNA via rapid thiazolidine formation. These AP–protein adducts are resistant to strand cleavage reactions that otherwise might induce genomic instability. ,,,, After repair synthesis restores the AP–protein adduct to the context of double-stranded DNA, the protein catalyzes its own dissociation from the DNA, leaving the AP site to be repaired via the base excision repair pathway. ,, The slow strand cleavage reactions that we observe for the thiazolidine adducts, with half-lives in the range of 12–60 h, are unlikely to be relevant to the properties of the SRAP proteins because these DNA–protein adducts are relatively short-lived, , and the microenvironment surrounding the thiazolidine residue in the active site of these proteins disfavors strand cleavage …”
Section: Discussionmentioning
confidence: 90%
“…74−77,79,83−85 Paulin et al used AP-oligonucleotide exchange reactions to show that DPC formation in single-stranded by HMCES and its bacterial orthologue YedK is a reversible process. 76,78,82 In accordance with Tolman's principle of microscopic reversibility (1925), dissociation of the YedK-AP DPC, like the formation process, is self-catalyzed by the active site residue Glu105 and, to a lesser extent, His160. 76 It was subsequently shown that reversal of the HMCES-AP DPC is similarly dependent upon catalysis by Glu127 and, to a lesser degree, His210, as well as the DNA-binding properties of the protein.…”
Section: T H Imentioning
confidence: 89%
“…78 Formation of the DPC by E127A and H210A mutants of HMCES occurs somewhat more slowly than the wild-type protein but is nonetheless complete within 10 min. 78 Formation of the YedK-AP DPC in single-stranded DNA, similarly, is a fast reaction. 76 The HMCES-AP DPC in single-stranded DNA is stable for hours and protects AP sites against endonucleolytic cleavage by APE1.…”
Section: T H Imentioning
confidence: 94%
See 2 more Smart Citations